2015
DOI: 10.1515/aoas-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

The productive lifetime of sows on two farms from the aspect of reasons for culling

Abstract: The aim of this study was to compare the characteristics of the productive lifetime (plT) of sows kept on two farms, from the aspect of reasons for culling. The study was based on data from animals from two breeding farms in hungary, using the data of 3493 crossbred dutch large white and dutch landrace sows (dlw × DL) between their first farrowing until the time of culling (2006 and 2012). For six years, the annual culling rate for both farms averaged 45%. The most frequent reasons for removal on both farms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…However, pigs at other stages of production may need special considerations during transport, due to their physiological conditions, health status, or age (21). For example, sows are most likely to be culled due to lameness or failure to rebreed (22, 23), and may have difficulties walking, and loading onto the truck. Many cull sows also have poor body condition (24), whereas obesity has been indicated as the main reason for culling boars (25) along with feet and leg issues (26).…”
Section: Methodsmentioning
confidence: 99%
“…However, pigs at other stages of production may need special considerations during transport, due to their physiological conditions, health status, or age (21). For example, sows are most likely to be culled due to lameness or failure to rebreed (22, 23), and may have difficulties walking, and loading onto the truck. Many cull sows also have poor body condition (24), whereas obesity has been indicated as the main reason for culling boars (25) along with feet and leg issues (26).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a culling percentage of 51% and mortality of 9% was reported in the U.S.A. (Mote et al, 2009). In Hungary, the corresponding figures were 45% and 16% (Balogh et al, 2015). In addition, we were able to obtain data only from volunteer herds, not from randomly selected herds, and this may have led to selection of better managed herds.…”
Section: Discussionmentioning
confidence: 97%
“…This may have contributed to a lack of estrus expression by gilts. Another survey at two farms in Hungary indicated that 40% of the culls were due to leg problems and 51% were due to reproductive problems [16]. …”
Section: Reasons For Removing Boars and Sows From The Breeding Herdmentioning
confidence: 99%
“…Sows get culled for being lame or failing to rebreed [15,16]. Body condition is not usually used as a reason for culling but sows may enter the transportation and marketing channels that have poor body condition.…”
Section: Reasons For Removing Boars and Sows From The Breeding Herdmentioning
confidence: 99%